"Micro" versus "small" family businesses: a multinational analysis. Issue 3 (17th August 2015) - Lussier, Robert N.; Sonfield, Matthew C.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to compare "micro" enterprise (0-9 employees) to "small" enterprise (10-49 employees) family businesses with regard to 12 important managerial characteristics in eight countries: Argentina, Croatia, Egypt, France, Kosovo, Kuwait, Serbia, and the USA (n=601). Design/methodology/approach – The research methodology was survey research. To statistical test 12 hypotheses, MANCOVA was run to compare differences between micro and small family business, while controlling for years in business. Findings – Six significant differences were: "small" firms are more likely to employ non-family member managers, are more likely to engage in the formulation of succession plans, are more likely to utilize outside advisory services, make greater use of sophisticated financial management methods, and have a more formal management style than "micro" firms; but the influence of the founder is greater in "micro" firms. Practical implications – For practitioners and consultants the findings of this study should enable family business owner/managers, and their advisors, to better understand the possible impacts of moving from a "micro" level to a "small" size level, and thus lead to more effective family business management. Originality/value – This research fills a gap in the literature, as there has been minimal prior research with the specific focus of comparing "micro" vs "small." Thus, it develops a foundation for further study in this area.